Identification and description of controlled clinical trials published in Physiotherapy journals in Spain. Issue 1 (14th September 2015) - Turrillas, Maitane; Sitjà‐Rabert, Mercè; Pardo, Hector; Vilaró Casamitjana, Jordi; Fort‐Vanmeerhaeghe, Azahara; Morral Fernández, Antonio; Cebrià i Iranzo, Maria Àngels; Bonfill Cosp, Xavier
Abstract: Rationale and objectives: The quantity and quality of research in physiotherapy has increased exponentially during the past decades. However, retrieving publications associated with this field of research is difficult. The aim of this study is to identify and describe controlled clinical trials (CCT) published in Spanish physiotherapy journals using electronic and handsearching strategies. Method: Observational study through which we identified eligible journals in order to retrieve CCTs using electronic and handsearching strategies, as proposed by the Cochrane Collaboration. A descriptive analysis of the main characteristics of these CCTs was completed. Results: Seventy‐eight CCTs were identified in 10 eligible journals, none of which were indexed in the major databases. 16.7% of the identified studies were multicentric. Traumatology and orthopaedics was the most studied field (33.3%) followed by neurology (15.4%). The most researched health problems were back pain (17.24%) fibromyalgia, arthrosis and stroke (6.8% each). Measured outcomes varied greatly, including pain control, functional mobility and quality of life. Most CCTs (64.1%) had a high risk of bias. Conclusions: The number of CCTs published in Spanish physiotherapy journals is limited. Handsearching these journals is essential, since none is indexed in major databases. In general, the identified CCTs carry a high risk of bias.